2014
DOI: 10.1183/09031936.00059414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of upper-airway stimulation for obstructive sleep apnoea on airway dimensions

Abstract: Upper-airway stimulation (UAS) using a unilateral implantable neurostimulator for the hypoglossal nerve is an effective therapy for obstructive sleep apnoea patients with continuous positive airway pressure intolerance. This study evaluated stimulation effects on retropalatal and retrolingual dimensions during drug-induced sedation compared with wakefulness to assess mechanistic relationships in response to UAS.Patients with an implanted stimulator underwent nasal video endoscopy while awake and/or during drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 35 publications
2
120
0
Order By: Relevance
“…In patients with moderate to severe OSA and specific clinical and anatomical characteristics, UAS therapy has previously been shown to provide multilevel (retropalatal and retrolingual) improvement in airway dimension and airflow by augmenting neuromuscular function of specific upper airway muscles while avoiding anatomy-altering surgery -dramatically reducing side effects, recovery, and risk. [21][22][23] Prior reports have also demonstrated significant and sustained reductions in polysomnographic measures of OSA severity over a 12-to 18-mo follow-up period. 7,8 At 18 mo, the median apnea-hypopnea index (AHI) was reduced by 67.4% from the baseline of 29.3 to 9.7/h, and the median 4% oxygen desaturation index (ODI) was reduced by 67.5% from 25.4 to 8.6/h.…”
Section: Discussionmentioning
confidence: 89%
“…In patients with moderate to severe OSA and specific clinical and anatomical characteristics, UAS therapy has previously been shown to provide multilevel (retropalatal and retrolingual) improvement in airway dimension and airflow by augmenting neuromuscular function of specific upper airway muscles while avoiding anatomy-altering surgery -dramatically reducing side effects, recovery, and risk. [21][22][23] Prior reports have also demonstrated significant and sustained reductions in polysomnographic measures of OSA severity over a 12-to 18-mo follow-up period. 7,8 At 18 mo, the median apnea-hypopnea index (AHI) was reduced by 67.4% from the baseline of 29.3 to 9.7/h, and the median 4% oxygen desaturation index (ODI) was reduced by 67.5% from 25.4 to 8.6/h.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Safiruddin et al showed that unilateral stimulation of the hypoglossal nerve increases airway area at multiple levels [39]. The degree of UA opening corresponded to higher amplitudes of stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…In most patients with a higher AHI, the obstructions are found on different levels such as the tongue base and the retropalatal region. Most importantly, opening the airway in an anterior-posterior dimension during hypoglossal nerve stimulation is relevant particularly concerning the role of airway shape for OSA therapies [39].…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ was used in another study describing upper airway crosssectional area very recently [18]. One co-investigator who was blinded to the AG results analyzed each image five times, and the mean was calculated.…”
Section: Image Analysismentioning
confidence: 99%